Systems and procedures and method study of Sanwa Wood Industries - Alejandro, Cherrie May; Berenguer, Abby; Francisco, Kathryn; Salva, Claire (College of Engineering, 1998)
Over the years, the development of systems and procedures and work study have earned recognition among various entities may it be a business enterprise or simply a service oriented firm. These are indeed effective tools in analysis of the activities and operations comprising the system toward efficiency. The study on Sanwa Wood Industries, a company that manufactures tables and panel furniture, presented here is an application of such techniques. At first an analysis of the major problems and difficulties present in the company was conducted. From these, the relationship among these problems was determined. After some evaluation, the group has arrived at various alternatives. In the end, the study was able to come up with modifications regarding some methods of production like machine and material handling. The study does not comprise a perfect solution to the problems but nevertheless tried to come closer to an ideal solution far better than the existing one.